Criminal Sanctions Model For Children Aged 15-18 Years As A Form Of Criminal Law Reform - Singh, Rahul; Syahrin, Alvi; Marlina, Marlina (jurnal.unprimdn.ac.id, 2025)
The tabulation of case data collected by the Indonesian Child Protection Commission (KPAI), the Directorate General of Corrections of the Ministry of Law and Human Rights, and the National Police's National Police Center (Pusiknas Polri) explicitly shows the high number of cases of children in conflict with the law and the high number of children in conflict with the law as perpetrators with very serious crimes. The data is also still collected data, which means that data in the field can be much larger than the data that has been recorded, so it requires special and serious attention. Several problem formulations were drawn for the research study, namely how the regulation of criminal sanctions for children and the urgency of formulating a model of criminal sanctions for children aged 15-18 years as perpetrators of crimes in Indonesia, how the concept of updating the model of criminal sanctions for children aged 15-18 years in Indonesia, and how the formulation of the model of criminal sanctions for children aged 15-18 years is appropriate to the ethics of national legal development in Indonesia. This research uses a normative juridical method with a conceptual approach and qualitative analysis of primary and secondary legal materials. The research results show that the provisions on criminal sanctions for children in the Child Protection and Child Protection Law are still rehabilitative and not fully proportional for children aged 15–18 who commit serious crimes. Therefore, it is necessary to formulate a new sanction model that is fairer, more educational, and has a deterrent effect. The proposed reform concept includes optimizing the principal penalty to two-thirds of the adult penalty, accompanied by additional community service and out-of-institutional guidance, and increasing the maximum sentence to 12 years for crimes punishable by death or life imprisonment.